PROCESSING AND FOOD SAFETY OF WHOLE CLEAN CUTTLEFISH (Sepia sp.) FROZEN WITH THE IMPLEMENTATION OF GMP AND SSOP - Panjaitan, Pola S. T.; Saputra, Sandy; Saputra, Rahmad Surya Hadi; Soeprijadi, Liliek (Universitas Mataram, 2025)
Indonesia has significant aquatic resource potential, especially in its marine waters. One of its leading fishery products is cuttlefish, which is abundant in Indonesian waters. This study aims to examine the characteristics of frozen Whole Clean Cuttlefish processed in accordance with Good Manufacturing Practices (GMP) and the Standard Sanitation Operating Procedure (SSOP). The implementation of GMP and SSOP is essential to ensure the quality and safety of fishery products, as fish-based products are highly perishable. Therefore, improving food safety standards is necessary to maintain the quality of frozen Whole Clean Cuttlefish for consumers.